New guidelines for diagnosis and treatment of insomnia - Pinto Júnior, Luciano Ribeiro (2010)
The Brazilian Sleep Association brought together specialists in sleep medicine, in order to develop new guidelines on the diagnosis and treatment of insomnias. The following subjects were discussed: concepts, clinical and psychosocial evaluations, recommendations for polysomnography, pharmacological treatment, behavioral and cognitive therapy, comorbidities and insomnia in children. Four levels of evidence were envisaged: standard, recommended, optional and not recommended. For diagnosing of insomnia, psychosocial and polysomnographic investigation were recommended. For non-pharmacological treatment, cognitive behavioral treatment was considered to be standard, while for pharmacological treatment, zolpidem was indicated as the standard drug because of its hypnotic profile, while zopiclone, trazodone and doxepin were recommended. ____________________________________________________________________________________________________________ ABSTRACT